A polyphenol-rich Calafate (Berberis microphylla) extract rescues glucose tolerance in mice fed with cafeteria diet. (April 2020) - Soto-Covasich, J.; Reyes-Farias, M.; Torres, R.F.; Vasquez, K.; Duarte, L.; Quezada, J.; Jimenez, P.; Pino, M.T.; Garcia-Nannig, L.; Mercado, L.; Garcia-Diaz, D.F.
Graphical abstract: The anti-inflammatory and glucose profile management effect of Calafate (Berberis microphylla) was assessed in vivo . C57BL/6 mice fed with cafeteria diet for 14 weeks, were administered with a characterized and polyphenol-pure Calafate extract (PPCE) for 4 weeks. PPCE administration recovered glucose tolerance and insulin-elicited AKT phosphorylation in white adipose tissue of high fat diet fed mice. Chow, chow-fed mice; CD, cafeteria diet-fed mice; IPGTT, intraperitoneal glucose tolerance test. Highlights: A polyphenol-rich Calafate extract reduced inflammation in obese mice. The intake of this extract improves glucose tolerance of this mice. The administered treatment improves blunted insulin pathway. Abstract: The establishment of a chronic inflammatory state in the adipose tissue contributes to obesity-associated insulin resistance. Hence, disrupting the inflammatory response elicited by obesity remains a relevant target to tackle the modern-world pandemic. We evaluated the anti-inflammatory and insulin-sensitizing effect of Calafate ( Berberis microphylla ) by producing and characterizing a polyphenol-pure Calafate extract (PPCE). C57BL/6 mice fed with cafeteria diet for 14 weeks were administered PPCE (50 mg/Kg/day) for 4 weeks. PPCE administration rescued glucose tolerance and insulin-elicited AKT phosphorylation in white adipose tissue of diet-induced insulin-resistant mice. Furthermore, the cafeteria diet-induced expression of TNF-alpha and F4/80 was attenuated by PPCE administration, suggesting that PPCE rescues insulin sensibility by ameliorating the obesity-associated inflammatory state. Altogether, our data shows that Calafate represents a natural source of polyphenols with glucose tolerance-improving properties in vivo, suggesting a potential use of PPCE as a complementary tool against insulin resistance.